2019
DOI: 10.31557/apjcp.2019.20.3.911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Supplementation on Ki-67 and VEGF Expression Levels and Clinical Outcomes of Locally Advanced Breast Cancer Patients Treated with Neoadjuvant CAF Chemotherapy: A Randomized Controlled Trial Report

Abstract: Background:Omega-3 is a polyunsaturated fatty acid with an ability to regulate cell proliferation and apoptosis through interaction with inflammatory mediators. The potential additional beneficial effects of Omega-3 on chemotherapy patients with breast cancer is not yet completely revealed.Methods:A double-blind randomized control trial (RCT) involving a total of 48 locally advanced breast cancer patients was conducted. Ki-67 and VEGF expressions, as well as overall survival of patients receiving neoadjuvant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 34 publications
1
34
0
2
Order By: Relevance
“…A spectrum of cancers including breast [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], head and neck [ 15 , 17 , 18 , 19 ], gastrointestinal [ 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], gastric [ 21 , 28 , 29 , 30 , 31 ], colorectal/rectal [ 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], esophageal [ 15 , 19 , 21 , 46 , 47 ], leukemia/lymphoma [ 48 ], lung [ 14 , 15 , 21 , 40 , 49 ,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A spectrum of cancers including breast [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], head and neck [ 15 , 17 , 18 , 19 ], gastrointestinal [ 14 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], gastric [ 21 , 28 , 29 , 30 , 31 ], colorectal/rectal [ 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], esophageal [ 15 , 19 , 21 , 46 , 47 ], leukemia/lymphoma [ 48 ], lung [ 14 , 15 , 21 , 40 , 49 ,...…”
Section: Resultsmentioning
confidence: 99%
“…Of the total supplementation, DHA concentrations ranged from 0 to 2 g, with 86% of the studies providing 1 g or less per day. When capsules were provided concomitant with chemotherapy the intervention length was 6–24 weeks and equivalent to the duration of chemotherapy [ 7 , 8 , 9 , 10 , 11 , 16 , 20 , 26 , 27 , 30 , 31 , 32 , 33 , 34 , 45 , 48 , 49 , 50 , 51 , 56 , 63 ]. In the absence of chemotherapy, supplementation was provided for 1–6 months [ 12 , 13 , 14 , 35 , 36 , 52 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Omega-3 fatty acids have been linked to protective roles in breast cancer progression, such as the inhibition of angiogenesis and metastasis ( Figure 1 ). Additionally, several studies have suggested an association between a higher omega-3 intake and a lower risk of breast cancer ( 129 , 130 ). Supplementation of omega-3 fatty acids in women undergoing surgery for locally advanced, invasive carcinoma resulted in decreased expression of both Ki-67 and VEGF compared to a control group ( 130 ).…”
Section: Mediators Of Vascular Integrity That Enhance Obesity-breast mentioning
confidence: 99%
“…Additionally, several studies have suggested an association between a higher omega-3 intake and a lower risk of breast cancer ( 129 , 130 ). Supplementation of omega-3 fatty acids in women undergoing surgery for locally advanced, invasive carcinoma resulted in decreased expression of both Ki-67 and VEGF compared to a control group ( 130 ). Furthermore, the omega-3 fatty acid supplementation group displayed a longer disease-free survival and overall survival ( 130 ).…”
Section: Mediators Of Vascular Integrity That Enhance Obesity-breast mentioning
confidence: 99%